Implications of Article 28 H Verse (1) UUD 1945 Related To State Responsibilities In The Pandemic of Covid-19 - Yusuf Mardhani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
The 1945 Constitution has regulated the State's obligation to fulfill the right to life of its citizens, namely in Article 28 paragraph (1) of the 1945 Constitution. "Everyone has the right to live in physical and mental prosperity, to live and get a good and healthy living environment and the right to obtain health services". This means that in relation to this concept, the government is fully tasked with fulfilling all aspects needed by the community to comply with the rules in the article. With the danger of infectious diseases like what is happening today, namely the presence of COVID-19, the government must work harder in fulfilling its obligations. Meanwhile, citizens have the right to sue the government when their constitutional rights are deemed neglected by the government. This study uses a descriptive normative method, namely by combining the analysis of a legal rule that has been in effect and presented using an explanation and depiction of the flow and the results of the author's analysis with in-depth data presentation. Citizens who consider the government not taking proper COVID-19 precautions, not fully serious in providing health services to citizens who test positive for COVID-19, or not maximizing efforts to prevent the spread of COVID-19, then these citizens can apply lawsuits against the government. The lawsuit is addressed to the State Administrative Court with evidences where when the lawsuit is granted by the court, the citizen can claim compensation against the government regarding the losses suffered by the citizen.